Brome Hay Cost-Return Budget in Central and Eastern Kansas - Fogleman, Sarah L.; Kilgore, Gary L. (My University, 2005)
This publication compares the income per acre and cost per acre of producing brome hay in central and eastern Kansas.
MF2143_2005_10
Keywords: MF2143; Crops; Economics; MF